Do regular high protein diets have potential health risks on kidney function in athletes? - Poortmans, J. R.; Dellalieux, O. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
Excess protein and amino acid intake have been recognized as hazardous potential implications for kidney function, leading to progressive impairment of this organ. It has been suggested in the literature, without clear evidence, that high protein intake by athletes has no harmful consequences on renal function. This study investigated body-builders (BB) and other well-trained athletes (OA) with high and medium protein intake, respectively, in order to shed light on this issue. The athletes underwent a 7-day nutrition record analysis as well as blood sample and urine collection to determine the potential renal consequences of a high protein intake. The data revealed that despite higher plasma concentration of uric acid and calcium, Group BB had renal clearances of creatinine, urea, and albumin that were within the normal range. The nitrogen balance for both groups became positive when daily protein intake exceeded 1.26 g á kgÐ1 but there were no correlations between protein intake and creatinine clearance, albumin excretion rate, and calcium excretion rate. To conclude, it appears that protein intake under 2.8 g á kgÐ1 does not impair renal function in well-trained athletes as indicated by the measures of renal function used in this study. Key Words: glomerular filtration rate, albumin excretion rate, nitrogen balance.